Coherent signal-subspace processing of acoustic vector sensor array for DOA estimation of wideband sources - Chen, Huawei; Zhao, Junwei (Signal processing, 2005)
This paper deals with the estimation of the direction of arrival (DOA) for wideband coherent sources using acoustic vector sensor array. By extending the idea of wideband focusing into acoustic vector sensor array processing, a wideband DOA estimation approach based on coherent signal-subspace processing is developed for acoustic vector sensor array. Finally, simulation results are presented, to compare the proposed method with its counterpart based on acoustic pressure sensor array, the advantages of the proposed algorithm are identified.